Presence and Creation: Conversation with Peter Brook - Pérez-Guillon, Pedro (Sens public, 2019)
Pedro Pérez-Guillon (Santiago, Chile, 1983), professor of art and architecture at the Catholic University of Temuco (Araucania), interviewed Peter Brook about the mysterious process of artistic creation. In this exchange, which is focused on Western thought on art and artistic creation, but also on millenary Eastern thought and the presence of spirituality in the artist, Peter Brook refers to his travels in the East, where he followed almost the same itinerary as that of Georges Gurdjieff, who inspired his film Encounters with remarkable men. The experiences and knowledge acquired during these different trips and stays in the East, as well as his own work on theater and cinema, feed this interview conducted in the framework of the Academy of Arts of New York (2016) and published today for the first time thanks to Sens Public. The adjustment of the original text in English and its translation into French and Spanish was provided by Chantal Waszilewska and Roberto Gac, in collaboration with Pedro Pérez-Guillon.